Profil musculaire isocinétique des athlètes de haut niveau en fonction de la pratique de sports différents: le football, le basketball, le handball, le volleyball, et le cyclisme - Menager, E.; Dauty, M. (Science & Sports, 2019)
Objective: To determine and compare the knee isokinetic profiles in accordance with the high level practice of basketball, handball, volleyball, cycling or football. Method: One hundred and nineteen professional athletes were included. Thirty practiced basketball (10 in A League, 10 in B League and 10 in First National League), twenty-one practiced handball (First League), thirteen practiced volleyball (A League), thirty practiced cycling (Continental Pro Tour) and twenty-five practiced soccer (First League). The age was 26±4 years old [18-38] for 186±13cm height [167-213], 84±14kg weight [63-120], and 23.8±1.9kg/cm2 Body Mass Index [19.2-28.6]. The knee strength was measured using a CybexNorm® isokinetic dynamometer at the beginning of sport season. Quadriceps and hamstring maximal strength was reported to the body weight for comparison. The isokinetic conventional ratios (hamstring-to-quadriceps) and the bilateral (quadriceps-to-quadriceps and hamstring-to-hamstring) ratios were calculated for the 60 and 180°/s angular speed. Results: Age, height and weight were different depending on the sports practiced. The 180°/s angular speed allowed a better identification of muscle profiles according to the sports practiced. The quadriceps relative strength of soccer players was greater than basketball, handball players and cyclist's ones. The hamstrings relative strength of soccer players was superior to the other sports except the handball players. The conventional and bilateral ratios were not different in accordance with the sport practice. Conclusion: Our study has quantified and compared the anthropometric characteristics and isokinetic values of high level athletes. Soccer players have an isokinetic profile different from other sports players, probably related to the specificity of this sport practice. These results can be used by coaches, physiotherapists and reference sports physicians in relation to the individual and collective sports that have been studied.